Re-do cytoreductive surgery for peritoneal surface malignancy: Is it worthwhile?. Issue 5 (October 2020) - Narasimhan, Vignesh; Cheung, Francis; Waters, Peadar; Peacock, Oliver; Warrier, Satish; Lynch, Craig; Michael, Michael; Ramsay, Robert; Heriot, Alexander
Abstract: Background and objectives: Cytoreductive surgery (CRS) with hyperthermic intraperitoneal chemotherapy (HIPEC) offers selected patients with peritoneal surface malignancies (PSM) an improved survival. However, a substantial proportion of patients develop peritoneal recurrence. There is limited data on the efficacy of iterative CRS and HIPEC in such patients. This study evaluates the safety, efficacy and outcomes after re-do CRS and HIPEC for PSM at a tertiary institute. Methods: Patients undergoing re-do CRS and HIPEC for recurrent PSM were included. Cases were grouped into the first and iterative cases and compared to evaluate differences in morbidity, survival and factors influencing survival. Results: One hundred and forty patients developed peritoneal recurrence after CRS and HIPEC. Thirty-seven patients underwent re-do CRS and HIPEC. The most common indication for iterative surgery was pseudomyxoma peritonei in 27 patients (73.0%). Median survival was 97 months for patients undergoing iterative surgery compared to 40 months for those who did not. Median survival following first and iterative surgery was 97 and 89 months, respectively (p = 0.15). Median progression-free survival after first and iterative surgery was 23 and 19 months, respectively (p = 0.47). At iterative CRS and HIPEC, incomplete cytoreduction (HR 12.82, 95% CI 1.64–100.35), increasing PCI (HR 1.13, 95% CI 1.04–1.22), in particular PCI >20 (HR 10.90, 95% CI 1.37–86.66) were factors associated with worse overall survival. Conclusion: In well selected patients, iterative CRS and HIPEC is safe, and can provide favorable survival with low morbidity. Completeness of cytoreduction and PCI are factors that influence overall survival.